(untitled) (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
An application of exams and courses scheduling is made using Vertex Graph Colouring, Particle Swarm Optimization, and Constraint Based Reasoning method to produce a valid and optimal exam and course schedule which can also fulfill the demands of special schedule and room needs. FTI Untar is used as a study case in this development. The results of the tests done for the courses scheduling of even semester of 2010 / 2011 till odd semester of 2012 / 2013, without collision of special preferences, show that on average there’s no hard-constraints (constraints that must be satisfied) violation, only 13% of soft-constraints (constaints that are attempted to be satisfied) violations between each course and 6% soft-constraints violation due to the poor preference score of the room or time used. Whilst, the results of the tests done for the exams scheduling of odd semester of 2011 / 2012 and 2012 / 2013 show that on average there’s no hard-constraint and soft-constraint violation between each course although there is still 1% soft-constraints violation due to the poor preference score of the room used. The development was tested to the Secretariat of Informatics Department in FTI Untar and obtain a positive response because of the user-friendly user interfaces and can help to accelerate the process of course, practicum, and exam schedule’s report making.